KFTGA: A tool for tracing knowledge flow and knowledge growth in knowledge sharing environment - S.M.F.D, Syed Mustapha (IOS Press, 2012)
Knowledge management is an interdisciplinary research area and it has been perceived in different perspectives by researchers and practitioners who come from various backgrounds. Nevertheless, the ultimate goal in knowledge management is to create a learning organization in a knowledge sharing environment. In a knowledge sharing environment, the learning communities are actively involved in building and developing the community knowledge through message postings, resource management and collaborative work besides performing the individual learning. A system, called KFTGA, has been built in this project that is capable to trace the knowledge flow of a pre-defined knowledge domain developed by the community members. Knowledge in this context is in the form of opinion, suggestions, and tangible objects from knowledge sharing activities which are traceable from the textual descriptions. Two salient aspects in KFTGA are having the ability to determine whether the knowledge that flows among the members is relevant to the knowledge context in the community and to trace whether there is a growth in knowledge building in relation to predefined topics. In order to achieve that, this paper describes three mathematical models for computing the relevancy of the knowledge flow, measuring the knowledge growth and examining the variations between documents. Finally, it elaborates how KFTGA can be applied in various knowledge sharing and knowledge flow model predominantly known as SECI model and its extended variations applied in virtual organizations, peer-to-peer team and multinational corporations.